Selected Works Vol 2 - Karl Marx; Frederick Engels; MARX(Karl); ENGELS (Frederick) (Moscow Progress Publishers, 1973)
This edition of the Selected Works by KArl Marx and Frederick Engels is an invaluable reader for students and others since it provides in full the key works of the two most influential writers in the socialist tradition. These include Marx's celebrated analysis of social class and political change, The Eighteenth Brumaire of Louis Bonaparte, Engel's Origin of the Family, a pioneering materialist history of gender relations, and their immortal polemic, the 1848 Manifesto of the Communist Party. These Selected Works form an ideal student reader, distilling the essentials from the bewildering expanse of Marx and Engel's writing. Spanning the diversity of their contributions to philosophy, political economy, history and critical theory, this volume offers the perfect introduction to the classic works of Marxism.
Keywords: Wages and Currency; Labouring Power; Supply and Demand